2005
DOI: 10.1289/ehp.8195
|View full text |Cite
|
Sign up to set email alerts
|

Thyroid-Hormone–Disrupting Chemicals: Evidence for Dose-Dependent Additivity or Synergism

Abstract: Endocrine disruption from environmental contaminants has been linked to a broad spectrum of adverse outcomes. One concern about endocrine-disrupting xenobiotics is the potential for additive or synergistic (i.e., greater-than-additive) effects of mixtures. A short-term dosing model to examine the effects of environmental mixtures on thyroid homeostasis has been developed. Prototypic thyroid-disrupting chemicals (TDCs) such as dioxins, polychlorinated biphenyls (PCBs), and poly-brominated diphenyl ethers have b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
166
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 189 publications
(174 citation statements)
references
References 56 publications
8
166
0
Order By: Relevance
“…Other studies used the MRL (Wade et al 2002) or ADI and two studies used a measure of human levels, human serum concentrations (van Meeuwen et al 2007) or background human daily intake (Crofton et al 2005). One study used a set concentration, 1mg/kg/day ).…”
Section: Experimental Studies Relevant To Low Dosementioning
confidence: 99%
See 2 more Smart Citations
“…Other studies used the MRL (Wade et al 2002) or ADI and two studies used a measure of human levels, human serum concentrations (van Meeuwen et al 2007) or background human daily intake (Crofton et al 2005). One study used a set concentration, 1mg/kg/day ).…”
Section: Experimental Studies Relevant To Low Dosementioning
confidence: 99%
“…There is good evidence that several chemicals can work together to induce reductions in thyroid hormone levels at doses where the individual chemicals are ineffective (Crofton et al 2005). (Crofton 2008) demonstrated that chemical substances may interact with the thyroid hormone pathways at different sites and via different mechanisms.…”
Section: Precursor Effectsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, thyroid hormones are of special importance in fetal development. During the first part of pregnancy, the fetus relies entirely on transplacental transfer of maternal thyroid hormones and thus on a normal maternal thyroid function, but maternal thyroid homeostasis is also contributing substantially to fetal development during the remaining part of pregnancy (15,24). Thus far, only few studies in humans on thyroid disrupting effects of phthalates have been carried out, whereas their adverse effects on rat's endocrine health are better investigated.…”
Section: Discussionmentioning
confidence: 99%
“…For example, PCB153 (a non-dioxin-like PCB congener) and TCDD produced a remarkable synergism in the EROD enzyme activity and hepatic porphyrin level, respectively (Bannister and Safe, 1987;van Birgelen et al, 1996). A synergistic decrease in the serum total thyroxine concentrations was found when using a mixture of 18 polyhalogenated aromatic hydrocarbons (dioxins, dibenzofurans, and dioxin-like and non-dioxin-like PCB congeners) (Crofton et al, 2005). A combination of TCDD and PCBs was also found to produce synergistic effects on the CYP1A1 expression and hepatotoxicity in Sprague-Dawley rats (Wang et al, 2011).…”
Section: Discussionmentioning
confidence: 99%